Studi komparasi pengaruh penggunaan variasi konsentrasi inhibitor amine oxide terhadap laju korosi pipa baja API 5L grade B di lingkungan fluida drain line - Dian Ahmad Sudali; Priyo Tri Iswanto (Badan Kerja Sama Teknik Mesin Indonesia, 2022)
API 5L Grade B Steel Pipes is one of the most used in pipeline system for oil and gas industry because it has the appropriate strength and characteristics. Nevertheless, API 5L Grade B Steel Pipes potential for corrosion due to working in a corrosive environment. One of the efforts that can be done to prevent corrosion in this piping system is the use of inhibitors. The purpose of this study was to study the effect of using variations in the concentration of amine oxide inhibitors on the corrosion rate of API 5L Grade B steel pipe in the drain line fluid environment. The inhibitors used in this study were organic inhibitors, namely amine oxide with a concentration variation of 0.5% and 0.9%. Corrosion measurement using Potentiodynamic Polarization method. Tests for composition, microstructure, Vickers hardness, and tensile tests were carried out to support the test data. The results showed that the corrosion rate of API 5L Grade steel pipe in a drain line fluid environment without inhibitors was 68.94 mpy. The addition of amine oxide inhibitor was effective in reducing the corrosion rate and the optimum concentration was obtained at a concentration of 0.9% with a corrosion rate of 8.16 mpy.